233 BISPHOSPHONATES: ANOTHER COMPLEX DRUG TO PRESCRIBE. (18th November 2021) - Mustafa, W; O'Byrne, R; Okpaje, B; Gabr, A; Ali, B; Mohamed, A; Cameron, S; Leahy, A; Fernandes, L; Mannion, M; Ryan, P; Ryan, S; et al.
Abstract: Background: Bisphosphonates provide effective treatment for osteoporosis. They accumulate a bone reservoir lasting for 3 years and beyond. The 2021 NICE guidelines recommend a medication review and a 'drug holiday' after 5 years of oral bisphosphonate therapy for low-fracture risk patients. Continuing treatment for high risk individuals is advised: age=/>75, previous hip or vertebral fracture, one or more fractures during treatment, recent DEXA scan with T score =/<−2.5, and/or current treatment with oral glucocorticoids. This retrospective audit aimed to assess compliance with NICE guidelines in a primary care setting. Methods: Data were collected using the Health One online medical record system in an urban general practice. Inclusion criteria: all patients =/> 65 years old, prescribed oral bisphosphonate therapy for osteoporosis for >5 years. Exclusion criteria: deceased, did not attend clinic >1 year, patients on bisphosphonate treatment for conditions other than osteoporosis. Results: 137 patients with a history of bisphosphonate therapy were identified. 76 patients were on bisphosphonate treatment for greater than 5 years. Of the 76 patients, 33 were classified as low-fracture risk and appropriately commenced a drug holiday, while 22 correctly remained on bisphosphonates due to a high fracture risk. The remaining 21 patients inappropriately continued therapy without receiving a medication review, repeat DEXA or fracture-risk assessment. Conclusion: One third of patients on bisphosphonates beyond 5 years were not assessed for a drug holiday. The aim of a bisphosphonate 'drug holiday' is to reduce poly-pharmacy and prevent rare but serious long-term adverse events (such as atypical fractures, osteonecrosis of the jaw, gastric cancer and atrial fibrillation). Factors which had an impact on inappropriate prescribing should be assessed. Incorporating computer-based prescribing alerts could support safe prescribing practices.